ETIKA ISLAM DAN EKONOMI KERAKYATAN - Musa Asy'ari (UGM, 1999)
In a new Indonesia format, there appears a great desire to accelerate people's economy as the basis of the economic stability and national defense. This is due to the fact that indicates by the weakness of the fundamentals of the national economy in which small and mediom enterprises cannot get a chane to develop to a maximum.